The China Challenge Sino-Canadian Relations in the 21st Century - Cao, Huhua (University of Ottawa Press / Les Presses de l'Université d'Ottawa, 2011)
With the exception of Canada's relationship with the United States, Canada's relationship with China will likely be its most significant foreign connection in the twenty-first century. As China's role in world politics becomes more central, understanding China becomes essential for Canadian policymakers and policy analysts in a variety of areas. Responding to this need, The China Challenge brings together perspectives from both Chinese and Canadian experts on the evolving Sino-Canadian relationship. It traces the history and looks into the future of Canada-China bilateral relations. It also examines how China has affected a number of Canadian foreign and domestic policy issues, including education, economics, immigration, labour and language. Recently, Canada-China relations have suffered from inadequate policymaking and misunderstandings on the part of both governments. Establishing a good dialogue with China must be a Canadian priority in order to build and maintain mutually beneficial relations with this emerging power, which will last into the future.